2011
DOI: 10.4061/2011/974361
|View full text |Cite
|
Sign up to set email alerts
|

Function and Comorbidities of Apolipoprotein E in Alzheimer′s Disease

Abstract: Alzheimer's disease (AD)—the most common type of dementia among the elderly—represents one of the most challenging and urgent medical mysteries affecting our aging population. Although dominant inherited mutation in genes involved in the amyloid metabolism can elicit familial AD, the overwhelming majority of AD cases, dubbed sporadic AD, do not display this Mendelian inheritance pattern. Apolipoprotein E (APOE), the main lipid carrier protein in the central nervous system, is the only gene that has been robust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 358 publications
1
33
0
Order By: Relevance
“…The distribution of ApoE alleles in this set of patients is consistent with the literatures reported that higher number of E4/E4 alleles exhibited in AD patients than those of the none-AD subjects [31,32]. It has been known that E4 allele of ApoE protein is less efficient in proteolysis of beta amyloid, thus increases the brain amyloid deposition in individuals with this gene variant [33]. Interestingly, the patients with double E4 alleles in both AD and NC groups exhibited low levels of amyloid antibodies in the serum in this study.…”
Section: Discussionsupporting
confidence: 89%
“…The distribution of ApoE alleles in this set of patients is consistent with the literatures reported that higher number of E4/E4 alleles exhibited in AD patients than those of the none-AD subjects [31,32]. It has been known that E4 allele of ApoE protein is less efficient in proteolysis of beta amyloid, thus increases the brain amyloid deposition in individuals with this gene variant [33]. Interestingly, the patients with double E4 alleles in both AD and NC groups exhibited low levels of amyloid antibodies in the serum in this study.…”
Section: Discussionsupporting
confidence: 89%
“…The E4 allele of apolipoprotein E, the major lipid carrier in the central nervous system, has been consistently identified as the major genetic risk factor for AD, although it is not specific for this disorder [4345]. Other genetic factors also are involved in AD [4,9].…”
Section: Evidencementioning
confidence: 99%
“…The exact mechanism by which ApoE mediates cellular cholesterol efflux and whether this cholesterol efflux is isoform-specific is still unknown. The most consistent explanation for ApoE-mediated cholesterol efflux had relied on the intracellular association of ApoE with cAMP-induced ABCA1, which induces increased secretion of ApoE and catalysis of an initial transfer of cholesterol to the lipid poor ApoE ( 16 ) . Doubt has been cast on the sole regulation of cholesterol efflux by ABCA1, leading to the recognition of ABCG1 as finalizing the full transfer of this cholesterol to the apolipoprotein ( 16 ) .…”
Section: Discussionmentioning
confidence: 99%
“…ApoE displays genetic polymorphism with three common alleles namely, ε2, ε3, and ε4 in a single gene-locus in chromosome 19, giving rise to 3 homo-zygous (apoε2/ε2, apoε3/ε3, apoε4/ε4) and 3 heterozygous genotypes (Apoε2/ε3, Apoε2/ε4, Apoε3/ε4) ( 15 ) . Variants of this gene account for more genetic differences in cholesterol metabolism than any other gene ( 16 , 17 ) . Apoε3 genotype is reportedly selected for its positive effects in cholesterol control and for reducing the risk of various diseases ( 13 ) .…”
Section: Introductionmentioning
confidence: 99%